Thermophysical and volumetric study of mixtures p-cymene + propan-1-ol at several temperatures and atmospheric pressure. Modeling with COSMO-RS. (August 2018) - Martínez-López, José F.; Pardo, Juan I.; Liu, Sichen; Mainar, Ana M.
Graphical abstract: Highlights: Cp, m, of the binary mixture p-cymene (1) + propan-1-ol (2), have been determined in the temperature range (298.8–328.5) K. Experimental densities were measured at the same temperatures in the whole composition range. C p, m E are positive in the whole composition range and increase as temperature rises. COSMO-RS were tested to predict C p, m E showing acceptable deviations from experimental data. Abstract: Experimental isobaric molar heat capacities at atmospheric pressure have been determined for the mixture p-cymene + propan-1-ol every 10 K in the temperature interval (298.8–328.5) K and over the entire composition range with a Calvet type calorimeter. Densities, necessary for calculating heat capacities, have been also measured in similar conditions. Excess molar volumes have been calculated from densities. They are positive at (318.15 and 328.15) K and sigmoidal at (298.15 and 308.15) K with negative values in the zone very rich in propan-1-ol. Excess molar heat capacities have been calculated from the molar heat capacities and show positive values. Both excess molar properties increase as the temperature rises at a given molar fraction. Excess properties are discussed in terms of intermolecular interactions. The solvation model COSMO-RS has been applied to predict the excess molar heat capacities, being the quantitative predictions rather poor.